Hemodynamic effects elicited by microinjection of glutamatergic agonists into NTS of conscious rats - Dias, Ana Carolina Rodrigues [UNIFESP] (2001)
In this study, we characterized the arterial pressure, heart rate, and regional vascular conductance responses elicited by unilateral microinjection of ionotropic glutamatergic agonists N-methyl-D-aspartic acid (NMDA and non-NMDA) into the nucleus of tractus solitarius (NTS) of conscious rats. Microinjections of NMDA and S-alpha -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) caused changes in mean arterial pressure (MAP). Lower doses elicited decreases in MAP, whereas higher doses elicited biphasic responses (decreases followed by increases). Both agonists induced bradycardia and elicited dose-dependent vasoconstriction in the renal, mesenteric, and hindquarter beds. AMPA elicited delayed vasodilation in the hindquarter bed but NMDA did not. Bradycardia and initial hypotension produced by each agonist were abolished by systemic administration of the muscarinic antagonist methylatropine. However, methylatropine did not affect either the vasoconstriction or the vasodilatation. The contrasting hemodynamic effects produced by NMDA and AMPA could be caused by activation of differential subsets of NTS neurons. Preferential activation of one subset could produce the NMDA-related responses, whereas activation of another subset would elicit AMPA-related responses.